Students' and parents' perceptions of trilingual education in Hong Kong primary schools. Issue 4 (1st October 2020) - Wang, Lixun; Kirkpatrick, Andy
ABSTRACT: After the handover back to Mainland China in 1997, the Hong Kong government adopted a 'biliterate and trilingual' policy to help Hongkongers develop an ability to read and write Chinese and English, and to speak and understand Cantonese, English and Putonghua. However, there are no clear government guidelines on how and when the three languages should be introduced and taught in primary schools. Based on a survey of 155 Hong Kong primary schools, it was found that individual schools have adopted their own medium of instruction (MoI) policies, but these policies are decided by the school policymakers, without much consultation with the students and their parents. In this study, questionnaire surveys and interviews on students' and parents' perceptions of trilingual education were conducted in three case-study primary schools. The research findings suggest that students' and parents' views towards the use of different MoIs vary, which will be discussed in the paper in detail. Schools need to take these factors into consideration when developing MoI policies.